Doula - a new model of delivery (continuous, nonprofessional care during the delivery) - Guzikowski, Wojciech (Česká gynekologie, 2006)
In the last few years world literature examined advantages related to the presence and support of an nonprofessional person (doula) during a delivery. Aside from encouraging the husbands to take an active part in the delivery there was a rise in popularity of doula's help. The results of frequency questionnaire analysis show that in Poland parturients, first and foremost, expect support of a professional personnel (midwife, midwifery students).
Keywords: otcové; Humans; Fathers; porod; lidé; průzkumy a dotazníky; Pregnancy; Poland; těhotenství; Surveys and Questionnaires; Nurse Midwives; porodní asistentky; Parturition; Polsko